THE CHOICE OF SURGICAL TACTICS BASED ON THE RESULTS OF PIGMENTED LIMPHOGRAPHY FOR PATIENTS WITH LOCALLY ADVANCED PROXIMAL GASTRIC CANCER - M. O. Maksimov; S. A. Tuzikov; G. N. Strizhakov; E. O. Rodionov; S. V. Miller (Сибирский онкологический журнал)
Introduction. The lack of low-cost and available methods for the diagnosis of lymph node metastasis from gastric cancer and the standards of surgery for proximal gastric cancer is a hot topic for research. the aim of research is to study the effectiveness of the method of pigment lymphography and to develop criteria for determining the extent of surgery in the treatment of locally advanced proximal gastric cancer. Material And Methods. The study included 68 patients with locally advanced proximal gastric cancer. All patients were divided into 2 groups according to the extent of surgery: proximal subtotal gastric resection and gastrectomy. For intraoperative detection of lymph node metastases, the method of peroral pigmented lymphography was used.Results. The sensitivity, specificity and accuracy of pigment lymphography in detecting lymph node metastases were 99.0 %, 89.8 % and 93.4 %, respectively. The developed algorithm for the choice of the extent of surgery for proximal gastric cancer demonstrated advantage of proximal subtotal resection over gastrectomy in terms of overall survival (66.4 ± 13.2 % versus 48.7 ± 16.9 %, p=0.021). Conclusion. Peroral pigmented lymphography was shown to be an effective method in detecting lymph node metastases from gastric cancer.  Proximal subtotal gastrectomy in patients with locally advanced gastric cancer improved long-term treatment outcomes.